New stable isotope data and fossils from the Hirnantian Stage in Bohemia and Spain: implications for correlation and paleoclimate - Mitchell, C. E.; Štorch, P. (Petr); Holmden, C.; Melchin, M. J.; Gutiérrez, J. C. (2011)
Combined biostratigraphic, sequence stratigraphic and carbon isotope records from the Barrandian area, Bohemia revealed further details on Hirnantian δ13C excursion (HICE) and improved correlation with rock formations deposited in the Late Ordovician palaeotropics. Carbonaceous and highly fossiliferous condensed Perník Bed of the uppermost Králův Dvůr coincides with rising limb of the large positive δ13C excursion and may result from cooling and increased aridity associated with continental ice-cap growth. It is suggested that other cool water carbonates of the peri-Gondwanan Europe may reflect a similar genesis. New data also improved sequence-stratigraphic correlation with Hirnantian rocks at Anticosti Island.